Elaboración de un plan mantenimiento para los equipos del área de trituración de la empresa constriturar S.A.S. (2018)
To carry out the maintenance plan for the company's crushing area Constriturar S.A.S began with the data collection during 2 months, and from this have the necessary information to start the development of the project. Then the crushing process used by the company and the equipment was described that are part of the crushing area of line A, which are going to intervene, observing the current state of maintenance. A coding process was created for the teams, the criticality was established for each one and in this way determine for which equipment the plan. After this he elaborated the analysis of the fault and the logical tree of decisions respectively.